The first radiocarbon dates for the Globular Amphora culture cemetery in Sadowie in the Sandomierz Upland - Pasterkiewicz, Wojciech (the Authors, 2020)
The article presents new results of radiocarbon dating for the settlement of the Globular Amphora culture from the Sandomierz Upland area. These are three determinations obtained for animal graves (No. 4, 7 and 11) coming from the site 23 in Sadowie near Opatow, where traces of a vast cemetery were discovered. 14C dating was established in the Poznań Radiocarbon Laboratory. The received values were verified by indicating diagnostic features in the composition of artefacts that are referenced in groups of other features of the Globular Amphora culture.
Keywords: Globular Amphora culture; Sandomierz Upland; radiocarbon dates